Evaluación experimental del desempeño energético de un congelador comercial usando R1234yf a diferentes niveles de carga térmica (2021)
The use of low GWP refrigerants has been extended around of world due to new environmental policies in the last decade. In this sense, commercial refrigerants that are replacing R134a have a principal characteristic of a low global warming potential (GWP). This paper presents an experimental study of energy performance on a commercial freezer using R1234yf as a replacement to R134a considering three thermal load conditions: without thermal load, medium load thermal load, and full thermal load. Results showed that the use of R1234yf promotes a reduction in the internal temperature on the freezer which is 2.3% lowest cold R134a, while the steady thermal time gets with R134a is lower than R1234yf in 11.1%, 11.7%, and 4.4% respectively for each thermal load level.